Photoplethysmographic signal analysis using systolic and diastolic peaks - Baladjee, Jaisankar (2016)
Pulse Oximeter (PO) is a non-invasive device, used for measuring Oxygen saturation (SpO2), which refers to the concentration of oxygen in blood. Clinically, Pulse Oximeter is used to measure and display both SpO2 and Heart rate, most useful in Intensive Care Units. In this dissertation, a laboratory Pulse Oximeter has been used for measuring PPG signal, which is acquired with the help of LabVIEW NI SignalExpress. This acquired signal is generated as a text file by the software, which is later read and processed using MATLAB. This dissertation involves developing a suitable algorithm to process the Photoplethysmograph (PPG) signal obtained from pulse oximeters, to extract the breathing rate and the heart rate. Also, the Heart Rate Variability (HRV) is studied using spectral analysis. One drawback in the process of pulse oximetry is the presence of motion artefacts during measurement. The algorithm to be developed in this dissertation aims at removing the effects of motion artefacts in the process of extracting the breathing rate and heart rate. The extracted breathing rate and heart rate has been checked against manual and medical methods to ensure the correctness of results. Many algorithms have been proposed for extracting the breathing rate and heart rate. But, only the systolic peaks have been given importance in those algorithms. In this dissertation, the diastolic peaks has been given equal importance. The diastolic peaks are processed similar to the systolic peaks, and the results from the diastolic peaks are checked against the results obtained from systolic peaks. A spectral correlation is done to analyze the degree of correlation between them.